Analysis of Performance of University Groups Belonging to "Leadership in the Region and/or Industry" Track of "Priority 2030" Program - A. I. Guseva; V. M. Kalashnik; V. I. Kaminsky; S. V. Kireev (Moscow Polytechnic University, 2022)
This article presents the comprehensive study results of the performance of universities which are the winners of the "Leadership in the region and/or industry" track of the "Priority 2030" program. The research included a comparison of the results of 3 groups of universities of this track, determined by the results of the competition. The participation of these groups of universities in the main strategic initiatives in the field of the higher education system development in 2006-2020 is considered; indicators for the main areas of university activities were selected and grouped, namely, educational, scientific and innovation, international and financial. The comparative analysis of aggregate indicators of recent years is based on the Displaced Ideal Method. This made it possible not only to determine the current positions of universities belonging to the examined track, but also to identify a number of problems in their activities that need to be solved in the coming years to strengthen their contribution to the socio-economic development of the regions. The results of the comprehensive analysis can be used not only by the current participants of the "Leadership in the region and/or industry" track of the "Priority 2030" program, but also by universities that only plan to take part in this program in the near future and the expert community engaged in research in the field of higher education development in Russia.